Compositional Determination of Vinyl Acetate/Vinyl Benzoate Copolymer by Fourier Transform Infrared Spectroscopy - Poorya Bigdeli; Mahdi Abdollahi; Mahmood Hemmati (علوم و تکنولوژی پلیمر, 2015)
Relating polymer structure to its performance properties is a primary motivation for determining the structure of a polymer chain. If a polymer chain is completely characterized and the structural basis of its properties is known, one can optimize and control polymerization to produce the best possible properties from the chemical system. Infrared (IR) spectroscopy represents a powerful technique for characterization of the polymers. Several relative and absolute methods have been developed to determine the copolymer composition. Among these methods, IR technique as a relative method is a considerably faster and lower cost procedure than other methods like absolute nuclear magnetic resonance (NMR) analysis. In the present work, vinyl acetate/vinyl benzoate copolymers were synthesized by reverse iodine transfer polymerization (RITP) with different molar ratios of comonomers in the initial feed in the presence of iodine as in situ generator of the transfer agent and 2,2′-azobis(isobutyronitrile) as the initiator at 70˚C. Fourier transform infrared (FTIR) spectroscopy was used to determine the composition of the vinyl acetate/vinyl benzoate copolymers. Based on the five copolymers with known compositions determined by 1H NMR spectroscopy, a FTIR calibration curve was obtained. The composition of the synthesized vinyl acetate/vinyl benzoate copolymers with unknown compositions was then determined from the calibration curve and FTIR data. Feed composition and individual and overall molar conversions of the comonomers were calculated after determining the copolymer composition. The results obtained from the FTIR method were in good agreement with those obtained theoretically, indicating the accuracy of the method presented in the present research.